Turning reflection into learning: a practice development tool for midwifery students. Issue 3 (3rd May 2020) - Austin, Diana; Gilkison, Andrea; Clemons, Janine
ABSTRACT: A Practice Development Tool (PDT) was developed to assist midwifery students to reflect in a way that would contribute to the development of their practice. A survey was undertaken to explore midwifery students' experience of using this tool across the three years of their undergraduate programme. While a simplified model using reflection to develop practice was helpful, this was alongside the significant contribution of the relationship with the educator who supported them in practice and provided feedback on their use of the tool. The students indicated that they became better at reflecting, identifying their strengths and areas for improvement, and their ability to plan for change within the midwifery programme. The need to provide scaffolding of the elements within the tool, and subsequently to improve the education on the use of the tool at each year, was highlighted for future development.